Whatsapp sebagai Platform Penyebaran Informasi dan Berita di Kalangan Remaja Mahasiswa Pendidikan Sosiologi - Riri Aas Astria; Septi Kuntari (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
The development of digital technology has transformed the way students communicate and access information, with WhatsApp being one of the most widely used platforms. Among Sociology Education students at Universitas Sultan Ageng Tirtayasa, WhatsApp is not only used as a communication tool but also serves as a primary medium for disseminating academic and social information. This study aims to examine the role of WhatsApp in information distribution and to understand how students evaluate and filter the information they receive. This research employs a qualitative approach with a case study method through in-depth interviews, observation, and documentation. Data analysis is conducted using the Miles and Huberman model, supported by Rogers’ Diffusion of Innovation theory. The findings indicate that WhatsApp plays a significant role in supporting academic activities, such as delivering information, coordinating tasks, and sharing learning materials. However, the rapid flow of information also increases the risk of spreading unverified information, highlighting the importance of strengthening students’ digital literacy.